Patient Preferences for Information Sharing During Pregnancy: A Survey of Postpartum Women [26M]. (May 2020) - Peahl, Alex; Novara, Alli; Moniz, Michelle; Smith, Roger; Heisler, Michele
Abstract : INTRODUCTION: Anticipatory guidance on pregnancy, childbirth and parenting is a key component of prenatal care. Our objective was to evaluate patients' preferences for information sharing during prenatal care. METHODS: We performed a cross-sectional survey of postpartum patients admitted for childbirth and postpartum recovery at a tertiary care center from May-June, 2019. We assessed which prenatal care resources patients found most helpful and preferable (i.e. "would use"), including in-person (e.g. provider, nurse), print (e.g. books, handouts), media (e.g. video, website, app), and prenatal classes. Validated demographics items were included. Analyses included simple descriptive statistics. RESULTS: Of 332 eligible women, 300 (90%) completed the survey. Average age was 30.4 (5.3), 70% of patients were white and 71% had private insurance. The most helpful and preferred sources of prenatal education were nurses and doctors (helpful: 97%, 89%; preferred: 97%, 89%). Over 50% of patients reported other educational resources were helpful and preferred, including books, booklets, and websites. Though many women reported phone apps and the electronic medical record portal were helpful, fewest women preferred them (46% and 40% respectively). Though many women reported prenatal classes were not helpful, over half of women desired breastfeeding (63%) and prenatal classes. (57%). CONCLUSION: Patients prefer prenatal education be delivered by their nurse and provider, but are open to other educational modalities. There is a disconnect between patient preferences for prenatal education materials and the perceived quality of currently available resources. Future work will investigate how to better tailor prenatal care education to patient preferences, clinic workflow, and actual use.